Coordenação intersegmentar entre úmero e escápula de indivíduos com e sem dor no ombro durante a realização de tarefas funcionais - Cabrini, Isabella (Universidade Federal de São Carlos, 2024)
The shoulder joint complex is responsible for positioning the upper limb in space, with the complete integration of the joints being essential for its proper functioning. In this way, humans are able to generate coordinated behavior patterns based on information from the environment and directed toward a functional goal. Changes in the scapulohumeral rhythm seem to be related to variations in the overall movement pattern. Objective: Characterize the intersegmental coordination of the shoulder complex during the performance of functional tasks. Methods: Eighteen individuals without shoulder pain were selected, and 3D scapular kinematics were recorded during the performance of four tasks: one with an internal focus (arm elevation in a self-selected plane) and three with an external focus (combing hair, placing an item on a shelf, and cleaning a window). Coordination between the humerus and scapula was determined for each task based on the primary movements of each segment. Upper limb disability was measured using the DASH (Disabilities of the Arm, Shoulder, and Hand) questionnaire. Results: The sample included 6 men and 12 women with an average age of 25 years. All data were collected with the individuals' dominant arm (right). The results did not show a significant difference in variability for any task. Conclusion: The pattern of intersegmental coordination may change based on the nature of the task, that is, the focus of the movement. Therefore, it becomes important to consider the focus of the movement in the assessment and intervention of upper limb motor function, taking into account that considering the context or pursuit of goals may be more effective, thereby increasing individuals' awareness of their personal objectives.
Intersegmental coordination between humerus and scapula in individuals with and without shoulder pain during the performance of functional tasks
Keywords: Articulação do ombro; Cinemática; Fenômenos biomecânicos; Shoulder joint; Kinematics; Biomechanical phenomena; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::CINESIOLOGIA